"A growing number of people are showing interest in astronomy": Floatin Hubble - Mahboob, Mahdin (The Daily Star, 2011)
Interview of Professor of AAZ Ahmed, Professor of Physics, BRAC University, Interview taken by Mahdin Mahboob.